Angger Pradata Akir: Peraturan Hukum di Kerajaan Jawa Sesudah Mataram - Pranidhana, Ugrasena (UI Scholars Hub, 2003)
This study describes Angger-angger Pradata Akir, a king’s law written in the late 18 century in Surakarta and Yogyakarta after the Mataram period. It seems that the Javaneese society at that time has already known a kind of law to control the officials of the kingdoms. In so far there was no law classification on public and private law e.z which begun in the modern law.